IMPLEMENTASI KEBIJAKAN PENGELOLAAN AIR LIMBAH DOMESTIK DI KABUPATEN BUNGO PROVINSI JAMBI - Ifan Dolly, Fajar; Poiran, Poiran; Nurhatisa, Nurhatisa (Jurnal STIA Bengkulu, 2025)
The research was motivated by the presence of domestic wastewater in Bungo Regency which has affected the quality of river water and surface water and has the potential to damage the environmental ecosystem. This research aims to find out how Bungo Regency Regional Regulation Number 5 of 2018 is implemented regarding domestic wastewater management and to find out what factors influence the successful implementation of domestic wastewater management policies in Bungo Regency. The method used in this research is qualitative with a descriptive data approach. Research was conducted at the Environmental Service, Housing and Settlement Service, restaurants, river watersheds (Batang Tebo and Batang Bungo watersheds), laundry businesses, motorbike repair shops, palm oil companies, traditional market environments and residential areas which became sources. from domestic wastewater. In determining the sample this research used techniques purposive And accidental sampling of course based on certain criteria or characteristics that are relevant and valid as well as informants who truly understand and know the topic in order to complete the required information and data. Meanwhile, the data collection techniques used in this research are observation, interviews and documentation. Meanwhile, for data analysis techniques, the Miles and Huberman model is used which consists of data collection activities, data reduction, data presentation, verification and drawing conclusions. The research results show that the implementation of Bungo Regency Regional Regulation Number 5 of 2018 concerning Domestic Wastewater Management is quite good. Several educational activities have been carried out by the local government in several schools, but these activities have not been carried out evenly across all schools in Bungo Regency. Next, the assistance activities carried out in making environmental permits (environmental approval documents) have been running and DLH has facilitated all stakeholders who process waste water management permits. Judging from the coordination between government agencies, namely the Department of Housing and Settlements (Perkim) and the Department of Public Works (PU), as well as related agencies, the coordination of the implementation of tasks regarding domestic wastewater management has not been carried out optimally. This means there is no coordination as a form of effort to prevent domestic wastewater pollution. Policy implementation is analyzed through five indicators according to Edward III, namely communication, resources, disposition, bureaucratic structure.